Synthesis and Multinuclear NMR Study of 4-Methylbenzoylmethylene-tri-ptolylphosphorane Ylide and its Related Complexes with Mercury(II) Halides - Sabounchei, S.J.; Dadrass, A.R.; Nemattalab, H. (Asian Journal of Chemistry, 2010)
The novel a-phosphorus ylide of (4-methylbenzoylmethylene- tri-p-tolylphosphorane) (MBTPPY) (1) is prepared by the reaction of 4-methylacetophenone with tri-p-tolylphosphine in chloroform as solvent. The complexes of the type (MBTPPY·HgCl2) (2), (MBTPPY·HgBr2) (3) and (MBTPPY· HgI2) (4) are prepared by the reaction of MBTPPY with mercury(II) halides in moderate to good yields.